A prospective study comparing intra-operative and postoperative complications in totally extra peritoneal repair vs extended totally extra peritoneal for inguinal hernia - Aggarwal, Priyesh; Kochar, Mahinder Pal; Sharma, Brijesh Kumar; Bansal, Aayush; Sharma, Sweksha (International Surgery Journal, 2024)
Introduction: Inguinal hernia repair is one of the most common surgical procedures worldwide. Total extra peritoneal repair (TEP) and Extended-TEP (eTEP) are widely used minimally invasive methods. TEP involves creating a space in the preperitoneal plane without entering the abdominal cavity, whereas eTEP extends this approach, allowing for a broader operative field.This study compares the intra-operative and postoperative complications of TEP and eTEP, contributing to the optimisation of inguinal hernia management. Methods: It is a prospective study. A total of 60 patients who underwent TEP and e-TEP for inguinal hernia, who fulfilled the inclusion criteria. Patients were randomised by simple random sampling technique and were divided into two groups of 30 each (group A-TEP and group B-eTEP). Data of both groups were compared and analysed for statistical significance using Chi square test and Student ‘t’ test. Result: The comparative analysis between TEP and eTEP procedures shows no significant differences in demographic parameters. However, eTEP demonstrates significantly shorter operative time and hospital stay, quicker return to work. Both procedures have similar rates of low intra-operative and postoperative complications, indicating comparable safety profiles. Conclusion: Our study suggest that both techniques are associated with low complication rates and good patient outcomes, with eTEP showing potential advantages in terms of pain, recovery and wider access. These findings help to take better surgical decision, to make and helped optimize patient care in inguinal hernia management.